PENGARUH KUALITAS LAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK SYARIAH DALAM MELAKUKAN TRANSAKSI DI MASA PANDEMI COVID-19 (Studi Kasus Mahasiswa Universitas Islam Malang Pengguna Mobile Banking) - Navilah Laila Wardani; Nur Diana; Harun Al Rasyid (El-Aswaq, 2020)
This study aims to determine the effect of the quality of mobile banking services on the satisfaction of Islamic bank customers in conducting transactions during the covid-19 pandemic. Samples were taken using purposive sampling method. The method used in this study uses quantitative methods with simple linear regression analysis techniques and hypothesis testing with SPSS. The results of data analysis show that the quality of mobile banking services simultaneously affects customer satisfaction in conducting transactions during the covid-19 pandemic. Partially, the quality of mobile banking services affects customer satisfaction in conducting transactions during the COVID-19 pandemic.